Prevention - Lawrenz W (Dynamic Media Sales Verlag, 2019)
Physical activity and exerciseare important for the physiological and psychological development of children and adolescents. Theyalreadyplay a significant role in enhancing and maintaining health in this age group. However, in adverse climatic conditions like heat and high humidity, intensive exercise, especially when involving large muscle groups, can be a risk for the health of children and adolescents, causing exertional heat illness.The mechanisms of adaptationto physical activity at high temperatures change during puberty. However, the thermoregulatory ability in children is as effective as in adults; comparable relative exercise intensity causes similar changes in body core temperature in both age groups. The risk for exertional heat illnessin children and adolescents is highest when vigorous exercise is performed in hot and humid environment, but it may also occur atmoderate temperatures. Tolerance for exercise in the heat shows great individual differences and can be influenced by training in adverse climatic conditions.Exertional heat illness in children and adolescents is preventable by different measures. There should be sufficient time for recovery between repeated exercise bouts. Children and adolescents should drink sufficient quantities regularly and providefor sun protection of head and skin. During all athletic events in the heat with participation of children and adolescents, trained personnel and facilities capable of effectively treating all forms of heat illness, should be readily available on site. KEY WORDS: Heat Tolerance, Heat Illness, Puberty